Sosialisasi Manajemen Pemasaran Yang Strategis Dalam Pengembangan Pesantren Modern Saifullah An Nahdliyah - Atika Aini Nasution; A’an Nurhadi; Muhammad Ras Muis; Muhammad Prasetyo Wibowo (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
This research aims to assess the impact of the implementation of measured marketing strategies in Pesantren Modern An Nahdliyah, particularly in increasing the number of male and female students (santri) and enhancing public awareness nationwide. The research methodology involves both quantitative and qualitative analyses, incorporating data collection from marketing campaigns, feedback from prospective students, and the evaluation of public responses. The findings indicate that the implementation of marketing strategies at Pesantren Modern An Nahdliyah has successfully achieved its objectives, leading to a significant increase in student enrollments and heightened awareness among the public. Digital media, including the official website, social media, and online advertising campaigns, proved to be effective tools in reaching the target audience. The success factors involve strong collaboration between the marketing team and the pesantren management, along with active involvement of the pesantren officials in promotional activities. However, challenges were identified in adapting to changing trends in digital marketing and increasing competition within the pesantren sector. Future opportunities lie in the development of creative content, collaboration with influencers, and the utilization of emerging technologies. Recommendations include enhancing collaboration with media outlets, optimizing online advertising campaigns, and continuous monitoring of digital marketing trends. This research contributes to a better understanding of the effectiveness of marketing strategies in religious educational institutions, with the hope that Pesantren Modern An Nahdliyah continues to thrive and becomes a nationally recognized center for education.